Preventing Turbine High Vibration by Upgrading the Balance Weight Material at PLTP Darajat - Ropandi, Opan; Hakim, Maman Mulyana; Baraka, Muhammad Aqmal (Journal of Mechanical Design and Testing, 2024)
Due to its direct contact with high- pressure steam, the turbine rotor is an essential part of geothermal power plants. A balance weight located in the fifth stage of rotor turbine to prevent initial unbalance in the turbine rotor. Due to erosion and sulfur attacks, the balancing weight of PLTP Darajat is frequently damaged, which is evident by the formation of unbalance. On December 2020, when shutting down, PLTP Darajat encountered considerable vibration disturbance, at 1400 RPM rotation, it reached 104 m [P-P]. It was essential to balance the turbine rotor by adding a new balance weight after a borescope test revealed that balance weight erosion was 50%. An examination of the shape, erosion resistance, and sulfur resistance of the turbine balancing weight material was done to reduce the likelihood of erosion disturbances. At one time. PLTP Darajat utilized materials including SS-410, Tungsten Alloy, and 17-4PH. In this research we used the balance weight of Inconel 625 material. Next, we tested the material based on the Chromium (Cr), Copper (Cu) and material hardness (HB) values. Inconel 625 at 23% had the greatest material composition based on Cr value, 17-4PH at 4% based on Cu value, and 17-4PH at 298 based on HB value, according to the study’s finding. With a combination of Cr 23%, Cu 0%, and HB 255, Inconel 625 material had the best combination. We conclude that a material's resistance to erosion and sulfur will increase with increasing Cr and Cu levels. Compared to other materials, Inconel 625 exhibits superior resistance to erosion and sulfur. By applying this material we were able to avoid an increase in vibration in the turbine and an increase in service hours of 281 hours.